Analysis of innovation readiness level in SME exporting crafts sub-sector on furniture in Yogyakarta - Lisa Safirah Bella Donna; Sugeng Santoso; Indah Kayani; Imanuel Cahyanugraha; Derri Arfiandi; Djujuk Aryati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
One of Indonesia's leading exports from the manufacturing industry is the furniture sector. Yogyakarta is one of the regions with the largest furniture exports in Indonesia. CV. CA is one of the creative economy actors in the craft sub-sector who has succeeded in creating a variety of simple and elegant products with quality and certified wood raw materials. This research method uses qualitative and quantitative approaches. CV CA develops products and carries out a level of readiness for innovation and competes with similar competitors. Based on the results of this study, CV CA's business processes are proven in the field and pass the competency. Therefore, through this research, we can find out what CV CA has implemented so that it can penetrate the export market and revive the SME’s of the creative economy industry.